A Novel Quick Screening Method for the Second Usage of Parallel-connected Lithium-ion Cells Based on the Current Distribution. Issue 3 (10th March 2023) - He, Kun; Tao, Shengyu; Fu, Shiyi; Fan, Hongtao; Tao, Yulin; Wang, Yu; Sun, Yaojie
Abstract : Battery screening is the key segment of secondary applications. The benchmark for conventional methods is mainly based on the series connection and makes parameter difference as the screening index a gold standard. However, because of self-balancing current in parallel connection, the existence of a certain degree of parameter difference is allowed and parameter difference may not be the best option, which leads to lower screening efficiency due to the higher uniform of parameters. This work firstly identifies the boundary of parameter difference and provides the ideal working point (IWP), which is related to maximum capacity utilization efficiency, as a novel screening index for parallel connection derived from the current distribution. A modified shepherd model is employed to calculate the IWPs and is verified that the maximum dynamic error is below 1.1%. Therefore, it is quick to achieve screening by judging whether the IWP falls within the normal working range. The results show that the maximum capacity utilization efficiency always occurs at the load current close to the IWP, which verifies the validity of IWP. Compared with the conventional method, the proposed method is validated based on a case study to improve screening efficiency and provides different ideas for flexible grouping.